STRATEGI PUBLIC RELATION DINAS SOSIAL PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN PONOROGO DALAM MEMBENTUK CITRA POSITIF DI MASYARAKAT - Gradian Pratama Ariyanto; Iswahyudi Iswahyudi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Public relations (PR) is a communication tool used by an institution or company to maintain good relations with the public. PR in the Social Services Department, P3A, plays a crucial role in building a positive image in society. The Social Services Department utilizes social media as a means of publicity to disseminate information about the institution, social programs, and activities. Through up-to-date content and responsiveness to questions and complaints from the public, the Social Services Department can shape a positive perception and enhance public appreciation for the institution. With effective PR, the Social Services Department can build a positive image and increase the trust and acceptance of the community towards the services provided. The objective of this study is to determine the strategies of public relations used by the Social Services Department to shape a positive image in society, using a descriptive method and qualitative approach. The findings of this research indicate that the Social Services Department employs segmentation methods in terms of targets and means, allowing the intended message to be maximally received by the audience